Penguatan Kesadaran Pendidikan tinggi dalam Keluarga melalui Pendekatan Spiral Sosiospiritualcultural: Studi Pengabdian Masyarakat di Desa Paring Lahung, Kabupaten Barito Utara: Strengthening Awareness of Higher Education in Families through a Socio-Spiritual-Cultural Spiral Approach: A Community Service Study in Paring Lahung Village, North Barito Regency - Widodo, Petrus; Sangalang, Ronald Hadibowo; Alexandro, Rinto; Asi, Natalina; Razzi, Fahrul; Tuah, Tuah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This Community Service activity aims to foster awareness of family education in Paring Lahung Village, Montallat Subdistrict, North Barito Regency, through a socio-spiritual-cultural spiral approach. This approach emphasises the synergy between social, spiritual, and local cultural values in building family self-awareness of the importance of higher education. The activity was conducted in three stages: preparation, implementation, and evaluation, involving 30 participants, comprising students and parents from SMAS PGRI Tumpung Laung. Data was collected through observation, interviews, and pre- and post-test questionnaires. The results showed an increase in students' motivation to pursue higher education (from 32% to 92%), as well as an increase in parental support for their children's education (from 80% to 92%). Participants also demonstrated a new understanding that education is not only an individual achievement but also a form of devotion to God and family. These findings confirm the effectiveness of the Spiral socio-spiritual-cultural approach as a model for family empowerment, grounded in local culture. This programme has the potential to be replicated in other rural areas with similar socio-cultural characteristics.